2002
DOI: 10.1080/00288330.2002.9517112
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, seasonality, lengths, and feeding behaviour of whale sharks(Rhincodon typus)observed in New Zealand waters

Abstract: Data from 36 whale shark (Rhincodon typus Smith, 1828) sightings off north-east North Island, New Zealand are summarised. Sightings were concentrated over the outer shelf and shelf break in areas influenced by the East Auckland Current at sea surface temperatures (SST) of 21-24°C. Sightings occurred from late spring to early autumn (November-April) but were most frequent in midsummer (February) when upwelling along the north-east shelf is weakest. The data indicate whale sharks occur off north-east New Zealand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 20 publications
1
30
0
7
Order By: Relevance
“…At least two of these sightings were of M. birostris (Table 1). Overall, the distribution of mobulid sightings is similar to that of other subtropical pelagic fishes off north-east North Island and generally coincides with the path of the East Auckland Current (EAUC) (Francis et al 1999;Duffy 2002). As the EAUC is usually located beyond the 1000 m isobath this probably explains why mobulid rays appear to be largely confined to an epipelagic habitat off northern New Zealand, whereas they are considered coastal species in most tropical regions (Compagno & Last 1999).…”
Section: Resultsmentioning
confidence: 84%
“…At least two of these sightings were of M. birostris (Table 1). Overall, the distribution of mobulid sightings is similar to that of other subtropical pelagic fishes off north-east North Island and generally coincides with the path of the East Auckland Current (EAUC) (Francis et al 1999;Duffy 2002). As the EAUC is usually located beyond the 1000 m isobath this probably explains why mobulid rays appear to be largely confined to an epipelagic habitat off northern New Zealand, whereas they are considered coastal species in most tropical regions (Compagno & Last 1999).…”
Section: Resultsmentioning
confidence: 84%
“…However, other organisms such as algae, squids, tunas and other nektonic species of medium or large size have been identified as potential prey (Compagno 1984;Taylor 1994;Norman 1999;Wilson and Newbound 2001;Duffy 2002;Stevens 2007). This information comes from the examination of the stomach contents of opportunistically studied stranded individuals (Compagno 1984;Last and Stevens 1994;Colman 1997) and from observations of individuals from coastal aggregations while feeding (Clark and Nelson 1997;Heyman et al 2001;Duffy 2002;Nelson and Eckert 2007;Rowat et al 2007). The sample size of stomach content studies is invariably limited to a single individual.…”
Section: Introductionmentioning
confidence: 97%
“…Sims et al (2003) reported a tagged basking shark that travelled at least 1878 km in 77 days, and a whale shark was shown to travel at least 1501 km from Ningaloo reef to the north-east Indian Ocean in 57 days (Wilson et al 2006). Migrations and seasonal aggregations of whale and basking sharks have been associated with physical and biological oceanographic conditions, with zooplankton abundance and composition appearing to play a major role in the movement, distribution and aggregations of these large filter-feeders (Heyman et al 2001;Duffy 2002;Sims et al 2006;Humphries et al 2010). Their movements were related to ocean currents and associated thermal fronts that stimulate, aggregate and transport food resources (Taylor and Pearce 1999;Wilson et al 2001;Cotton et al 2005;Sleeman 2007).…”
Section: Movementsmentioning
confidence: 99%